Primeiro registro de Limnocoris minutus De Carlo (Heteroptera: Naucoridae) no Brasil (Lundiana: International Journal of Biodiversity, 2007)
Thirteen macropterous specimens (nine males and four females) of Limnocoris minutus De Carlo, were collected in the Parque Municipal de Bacaba (14º43’17” S, 52º21’36” W), municipality of Nova Xavantina, state of Mato Grosso. This is the first record of this species in Brazil. This species was originally described from Paraguay and additionally recorded only in the Argentinean province of Corrientes.